Desmoplastic small round cell tumor of the kidney: a case report and discussion - Huang, Guizhen; Huang, Wenqian; Liu, Mingxue (Frontiers in Oncology, 2024)
A 13-year-old boy was admitted to the hospital with 1-month history of neck pain and a 2-week history of bilateral hip joint pain accompanied by low fever. Positron emission tomography-computed tomography (PET-CT) revealed the presence of a malignant tumor in the left kidney with metastases to the left renal hilum, retroperitoneum, para-aortic lymph nodes, and multiple bone sites throughout the body. Given that the patient’s left kidney capsule was intact and the boundary with surrounding tissues was clear, left nephrectomy was performed. Postoperative pathological diagnosis showed desmoplastic small round cell tumor (DSRCT) of the left kidney. CAV-VIP alternating chemotherapy was given 20 days after the first stage surgery. After the end of the 6th cycle, the patient underwent surgery again. The tumor in front of the aorta and postcava, the greater omentum, the retroperitoneal lymph nodes and the hepatic hilum lymph nodes, and the visible tumors in the abdomen were removed. CAV-VIP alternating chemotherapy was continued after the second stage surgery. At the end of the 4th cycle of post operation chemotherapy, radiotherapy was started. An abdominal CT scan conducted 11 months after second-stage surgery did not reveal any recurrence of abdominal tumors; however bone metastases persisted. The patient is currently receiving oral targeted therapy with anlotinib while ongoing follow-up continues.